Problemy wynikające z wejścia w życie ustawy RRFSR "O wolności wyznań" z dnia 25 października 1990 roku - Byś, Jelena (Prawo Kanoniczne, 2006)
Putting into effect a new law of the RSFSR ON FREEDOM OF RELIGION of October 25, 1990 caused many problems in public life and in life of religious communities in particular. This article introduces some of them, which became a subject of discussion. They are: interreligious equality, legislative acts concerning ownership of religious associations, access of religious associations to media and alternative military service. Formally the law of the RSFSR ON FREEDOM OF RELIGION of October 25, 1990 guarantees interreligious equality but in reality this principle is not respected. It has not been put into practice on the full scale and agreement in this sphere meets many obstacles or may be even impossible. A dislike of the Russian Orthodox Church for the Catholic Church increasing with ages is difficult to change. Catholicism is treated according to 19th century classification that means as a foreign and tolerated religion. However, the effect of the executive power activity as for tax exemption of religious associations was positive. Religious associations and their enterprises got right to provide their religious activity according to their statute benefiting from tax relieves and tax exemption. The things with restitution look worse. Though the law founds a basis for quick restitution of at least a part of seized property of religious associations reality appears to be different. Recognition of the priority of the Orthodox Church by the government and local authorities entails great privileges for it at the expense of other religious associations also as for restitution of cult erections, buildings and grounds that used to be their property. Right of religious associations for free access to media and founding their own ones though is guaranteed by the law in reality also meets with many difficulties. Having given such a right authorities prevent from exercising it. It results from over commercialisation of media and general reluctance, which consists in unnecessary complicating of formalities. But in spite of the difficulties the scale of broadcasting of religious media is constantly widening. The problem of alternative military service is still open in the Russian Federation. Legacy of long-term political up bringing do not let solve an increasing amount of problems in the army. A law on alternative military service would be a wise compromise between duty and legislation. Such a law would be able to lessen the tension in society and to protect rights of young citizens.